1995
DOI: 10.1007/bf02245095
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned ultrasonic distress vocalizations in adult male rats as a behavioural paradigm for screening anti-panic drugs

Abstract: Rats may produce ultrasonic vocalizations (USV) in threatening situations. USV of adult male rats in association with aversive stimulation was evaluated as a screening method for anxiolytic drugs. The triazolobenzodiazepine alprazolam, the 5-HT uptake inhibitors fluvoxamine and clomipramine, the mixed 5-HT/NA uptake inhibitor imipramine, the full 5-HT1A receptor agonists 8-OH-DPAT and flesinoxan, the partial 5-HT1A receptor agonists buspirone, ipsapirone and BMY 7378, the alpha 2-adrenoceptor agonist clonidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
47
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 52 publications
18
47
0
Order By: Relevance
“…Similarly, fluoxetine and paroxetine did not exhibit any anxiolyticlike activity in rat and mouse elevated plus-maze, and in fact produced anxiogenic effects (Silva et al 1999;Kurt et al 2000;Silva and Brandao 2000;Koks et al 2001). However, in contrast to the data generated in rat and mouse elevated plus-mazes, imipramine, fluoxetine, and paroxetine have been shown to produce anxiolytic-like actions in a number of other animal models of anxiety, including rat social interaction (Lightowler et al 1994), shock-or separation-induced vocalizations in rats and guinea pigs (Molewijk et al 1995;Molewijk et al 1996;Kramer et al 1998;Schreiber et al 1998;Podhorna and Brown 2000), and the four-plate test in mice (Hascoet et al 2000). Therefore, it is of interest that the gerbil elevated plus-maze appears to corroborate the anxiolytic findings with antidepressants in other invivo anxiety models and the recent findings in human patients.…”
Section: Stretch-attend Postures Head Dipsmentioning
confidence: 88%
“…Similarly, fluoxetine and paroxetine did not exhibit any anxiolyticlike activity in rat and mouse elevated plus-maze, and in fact produced anxiogenic effects (Silva et al 1999;Kurt et al 2000;Silva and Brandao 2000;Koks et al 2001). However, in contrast to the data generated in rat and mouse elevated plus-mazes, imipramine, fluoxetine, and paroxetine have been shown to produce anxiolytic-like actions in a number of other animal models of anxiety, including rat social interaction (Lightowler et al 1994), shock-or separation-induced vocalizations in rats and guinea pigs (Molewijk et al 1995;Molewijk et al 1996;Kramer et al 1998;Schreiber et al 1998;Podhorna and Brown 2000), and the four-plate test in mice (Hascoet et al 2000). Therefore, it is of interest that the gerbil elevated plus-maze appears to corroborate the anxiolytic findings with antidepressants in other invivo anxiety models and the recent findings in human patients.…”
Section: Stretch-attend Postures Head Dipsmentioning
confidence: 88%
“…Molewijk et al [72] suggested that conditioned ultrasonic vocalizations (USV) elicited by reintroducing adult rats into the environment in which they previously received inescapable footshocks may serve as a screening method for panicmodulating drug effects. However, as can be seen in Table 2, major discrepancies between animal studies and clinical ®ndings have been found with this model.…”
Section: Animal Models Of Panic Disorder Based On Conditioned Behaviormentioning
confidence: 99%
“…Instead, panic may even be exacerbated by buspirone or esinoxan [23,42,74,102]. Moreover, a single administration of clomipramine, imipramine,¯uvoxamine, mCPP and yohimbine, which have all demonstrated panicogenic properties following acute treatment, produced clear antipaniclike activity in the USV [72,91]. Taken as a whole, these ®ndings strongly question the predictive validity of USV as an animal model of panic.…”
Section: Animal Models Of Panic Disorder Based On Conditioned Behaviormentioning
confidence: 99%
“…3). The anxiolytic effects of many benzodiazepines on USVs have been previously shown in adult rats [1,2,10,16] and in rat pups [3,4,20], though the active doses were close to those that produce muscle relaxation and sedation. The dosage of diazepam (0.25-1.0 mg/kg, s.c.) used in the present study was supposed to have an anxiolytic effect, with neither muscle relaxation nor sedation occurring.…”
Section: Discussionmentioning
confidence: 43%
“…In view of the behavioral contexts in which USV are emitted, they are often interpreted as expressions of "fear" or "anxiety" [1,8]. Many attempts have been made to develop animal models to test the anxiolytic effects of drugs [2,6,10,16]. Suppression by anxiolytics of electric shockelicited or acoustic startle-elicited USV in adult rats have been proposed as animal models of psychopharmacology of anxiolytic action which are behaviorally compatible with human anxiolytic function.…”
Section: Introductionmentioning
confidence: 46%